THE EFFECT OF DEEP LEARNING-BASED TECHNICAL GUIDANCE ON TEACHING QUALITY AND STUDENT LEARNING OUTCOMES IN JUNIOR HIGH SCHOOLS IN PABUARAN DISTRICT - Yoga Rahayu; Ine Rahayu Purnamaningsih; Yuyun Yuningsih (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
Improving the quality of education is strongly influenced by the quality of teachers in implementing the learning process. One effort to enhance teacher competence is through Deep Learning-Based Technical Guidance (Bimtek). This study aims to analyze the effect of deep learning-based training on teaching quality and student learning outcomes in junior high schools in Pabuaran District, Subang Regency. The study used a quantitative approach with a survey method involving 60 teachers from five schools (four public and one private). Data were collected using a Likert-scale questionnaire and analyzed using linear regression. The results indicate that deep learning-based training has a positive and significant effect on teaching quality and student learning outcomes, with a coefficient of determination of 0.56. This shows that the training contributes 56% to the improvement of both variables. These findings suggest that continuous development of training programs tailored to teacher needs is essential to improve the quality of learning in schools. ABSTRAK Peningkatan kualitas pendidikan sangat dipengaruhi oleh kualitas guru dalam melaksanakan proses pembelajaran. Salah satu upaya untuk meningkatkan kompetensi guru adalah melalui Bimbingan Teknis (Bimtek) Berbasis Deep Learning. Penelitian ini bertujuan untuk menganalisis pengaruh pelatihan berbasis deep learning terhadap kualitas mengajar dan hasil belajar siswa di sekolah menengah pertama (SMP) di Kecamatan Pabuaran, Kabupaten Subang. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei yang melibatkan 60 guru dari lima sekolah (empat negeri dan satu swasta). Data dikumpulkan menggunakan kuesioner skala Likert dan dianalisis menggunakan regresi linear. Hasil penelitian menunjukkan bahwa pelatihan berbasis deep learning memiliki pengaruh yang positif dan signifikan terhadap kualitas mengajar dan hasil belajar siswa, dengan koefisien determinasi sebesar 0,56. Hal ini menunjukkan bahwa pelatihan berkontribusi sebesar 56% terhadap peningkatan kedua variabel tersebut. Temuan ini menyarankan bahwa pengembangan program pelatihan yang berkelanjutan dan disesuaikan dengan kebutuhan guru sangat penting untuk meningkatkan kualitas pembelajaran di sekolah.